2001
DOI: 10.1097/00006676-200110000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Inducible Nitric Oxide Synthase Reduces Bacterial Translocation in a Rat Model of Acute Pancreatitis

Abstract: Treatment with SMT appears to have ameliorated the course of acute pancreatitis; however, mortality was not affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…To investigate the pathophysiologic role of NO, a direct modulation of the NO pathway by application of either endogenous NOS inhibitors or NO donors was chosen in animal models of acute pancreatitis (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). However, controversial results were obtained as to whether the effects of enhanced NO generation are positive, negative, or negligible with respect to the development of local and systemic complications in the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To investigate the pathophysiologic role of NO, a direct modulation of the NO pathway by application of either endogenous NOS inhibitors or NO donors was chosen in animal models of acute pancreatitis (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). However, controversial results were obtained as to whether the effects of enhanced NO generation are positive, negative, or negligible with respect to the development of local and systemic complications in the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…L-NAME, competitive NOS inhibitor, has been shown to prevent lung injury in acute pancreatitis model (24). Further, animal studies also have documented that the administration of a selective iNOS inhibitor reduces bacterial translocation in acute pancreatitis and appears to have ameliorated the course of disease (25). Therefore, inhibition of NOS had favorable effects on pancreatitis which is complicated by the condition in which iNOS is expressed to produce excessive amounts of NO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In severe AP, inducible nitric oxide synthase (iNOS) overproduces NO. Excessive NO production cause pathological vasodilatation with capillary permeability increase and third space fluid loss 16 and tissue injury by NO derived free-radicals overproduction. AL MUFTI et al (1998) demonstrated an increase in iNOS activity associated to systemic NO increase and arterial hypotension in AP experimental models.…”
Section: Discussionmentioning
confidence: 99%